Polymeric and Ceramic Nanoparticles in Biomedical Applications - Aura-Ileana Moreno-Vega; Teresa Gómez-Quintero; Rosa-Elvira Nuñez-Anita; Laura-Susana Acosta-Torres; Víctor Castaño (Journal of Nanotechnology)
Materials in the nanometer size range may possess unique and beneficial properties, which are very useful for different medical applications including stomatology, pharmacy, and implantology tissue engineering. The application of nanotechnology to medicine, known as nanomedicine, concerns the use of precisely engineered materials at this length scale to develop novel therapeutic and diagnostic modalities. Nanomaterials have unique physicochemical properties, such as small size, large surface area to mass ratio, and high reactivity, which are different from bulk materials of the same composition. Polymeric and ceramic nanoparticles have been extensively studied as particulate carriers in the pharmaceutical and medical fields, because they show promise as drug delivery systems as a result of their controlled- and sustained-release properties, subcellular size, and biocompatibility with tissue and cells. These properties can be used to overcome some of the limitations found in traditional therapeutic and diagnostic agents. Nanotechnology is showing promising developments in many areas and may benefit our health and welfare. However, a wide range of ethical issues has been raised by this innovative science. Many authorities believe that these advancements could lead to irreversible disasters if not limited by ethical guidelines.